Biosecurity recommendations for the dentomaxillofacial radiological practice in the context of the COVID-19 pandemic - Carlos Martínez, Juan (2020)
The coronavirus disease 2019 caused by SARS-CoV-2, was declared a pandemic by the World Health Organization on March 11, 2020. Direct transmission occurs by respiratory route, while indirect transmission requires contact with the buccal, nasal or ocular mucosa with contaminated surfaces. In the presence of asymptomatic carriers that transmit the virus, all patients should be treated as possible sources of infection. In dental care, close contact with the patient and saliva puts staff at high risk for cross infection; The practice of dentomaxillofacial radiology in radiological centers or in the dental clinic is not exempt from this risk. The objective of the present literature review was to develop biosafety recommendations for the practice of dentomaxillofacial radiology. The recommendations related to areas and equipment indicate the importance of keeping these areas ventilated, with the least possible public traffic and the use of barrier protection, cleaning and disinfection of high-contact surfaces of radiological equipment. One of the critical measures to prevent transmission of the disease is hand washing and should be done by patients and staff. Extra-oral radiographic procedures should be prioritized over intra-oral ones. The use of teleradiology reduces the possibility of contagion by contact with contaminated surfaces and speeds up the flow of information between the clinician, the patient and the dentomaxillofacial radiologist.